2000
DOI: 10.1002/(sici)1097-0223(200004)20:4<347::aid-pd798>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute recurrent polyhydramnios and amniotic prolactin

Abstract: A 25 year-old patient in her third pregnancy presented with acute polyhydramnios at 24 weeks' gestation, which was the same time as in the two previous pregnancies. In both she had preterm premature rupture of membranes, preterm delivery and neonatal deaths. In the third pregnancy, amnioreductions combined with medical treatment resulted in the birth by Caesarean section of a normally formed live male at 31 weeks of pregnancy. Acute recurrent polyhydramnios is an extremely rare condition of unknown aetiology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Furthermore, only one lot of each product was tested and typically, the lot of a product corresponds to a single donor, and donor variability is known to exist. For example, the protein content of amniotic fluid has been shown to change with maternal hydration status and uterine perfusion, 39 as well as maternal prolactin levels. 17 Growth factor content in multiple amniotic membrane preparations (unprocessed, lyophilized, cryopreserved, or nitrogen-frozen) is also influenced by donor and gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, only one lot of each product was tested and typically, the lot of a product corresponds to a single donor, and donor variability is known to exist. For example, the protein content of amniotic fluid has been shown to change with maternal hydration status and uterine perfusion, 39 as well as maternal prolactin levels. 17 Growth factor content in multiple amniotic membrane preparations (unprocessed, lyophilized, cryopreserved, or nitrogen-frozen) is also influenced by donor and gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that decidual prolactin has an effect on amniotic permeability, although this is probably not the only hormonal or growth factor-related mechanism. 9 Uterine perfusion also impacts AF volume. Maternal dehydration leads to increased fetal plasma osmolality and increased fetal production of arginine vasopressin.…”
Section: Development Of Af and The Af Circulationmentioning
confidence: 99%
“…In another review by Shimuzu et al the cause of recurrent polyhydramnios was found to be HLA incompatibility of the couple [5]. Rare causes of polyhydramnios like fetal infection, Bartter syndrome, HLA incompatibility and abnormal amniotic fluid prolactin levels has also been reported in the literature [4,5,6]. Role of prolactin in the amniotic fluid affecting the permeability and fluid levels through receptors has been postulated to cause polyhydramnios.…”
Section: Reproductive System and Sexualmentioning
confidence: 99%
“…Role of prolactin in the amniotic fluid affecting the permeability and fluid levels through receptors has been postulated to cause polyhydramnios. In a review by De Santis et al the amniotic fluid levels were measured and were found to be high in women with recurrent acute polyhydramnios [4]. However, lack of data and heterogenous results do not justify measurement of amniotic fluid prolactin levels, electrolytes and HLA type for routine evaluation.…”
Section: Reproductive System and Sexualmentioning
confidence: 99%
See 1 more Smart Citation